The effect of COVID-19 on force majeure clause in international commercial contracts: its impact on public procurement in Latvia - Beļčikova, Darija (Riga Graduate School of Law, 2024)
The sudden appearance of the COVID-19 pandemic has caused remarkable disorganization to the global commercial world, dramatically influencing contractual arrangements throughout different sectors internationally. The pandemic has led to widespread neglect or disregard of contractual obligations amidst global shifts. Following the COVID-19 outbreak, other major events such as the Suez Canal incident and the War in Ukraine further disrupted the application of force majeure clauses in international commercial law. These changes stemmed from the pandemic and prompted individuals and organizations to invoke force majeure clauses due to unforeseen events occurring before contract completion, contingent on current circumstances. Public institutions engaging in contracts were compelled to adapt, leading to incomplete obligations. The concept of force majeure, typically governed by national laws, is a crucial aspect of contract analysis. One significant challenge posed by the pandemic is the evolving legal landscape surrounding force majeure cases, altering its historical interpretation.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Contract law; Force majeure; Covid-19; commercial contracts